Addressing Challenges in Implementing COSO-Based Internal Control in Public Universities - Razy Ulul Azima; Adam Zakaria; Ayatulloh Michael Musyaffi (Journal of State Economic Research, 2026)
This study highlights the challenges faced by public universities in implementing internal control systems based on the COSO framework. Increasing demands for accountability and transparency require institutions to ensure that internal control mechanisms are not only formally established but also effectively applied. This research aims to identify key issues in the implementation of COSO-based internal control and propose practical improvements. A qualitative descriptive approach was employed using data collected from documentation, interviews, and observations. The findings reveal that although internal control practices have been generally established, several challenges persist, including inconsistencies across units, limited responsiveness to emerging risks, and gaps in integrating risk assessment with control activities. This study emphasizes the need for strengthening coordination, improving adaptability, and conducting continuous evaluation to enhance the effectiveness of internal control systems in higher education institutions.